2006
DOI: 10.1007/s11515-006-0053-4
|View full text |Cite
|
Sign up to set email alerts
|

Cortical reaction and solicitation mechanism in Hemibarbus labeo ovum

Abstract: There are 1 to 4 rows and five types of cortical alveoli in the cortex of the pallas (Hemibarbus labeo) egg. From the outer to the inner of the cortex, the diameter of the cortical alveoli decreases gradually. We found a new structure named solicitation speckle at the low latitude of the animal pole and near the micropylar apparatus between the ovum envelope and cell membrane in the zygote of fish. The solicitation speckle similar to type I cortical alveoli was very purple in H.E chromosome, and it had no obvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Owing to environmental pollution, overfishing, and other factors, there has been a sharp decline in the wild resources of H. labeo in many rivers. The artificial breeding of H. labeo has been performed in different regions, such as the Fujiang, Wusuli, Yalu, Liaoning, Oujiang, and Qiantang Rivers, to save this precious resource [21][22][23][24][25]. Moreover, H. labeo has the wide distribution, medium life span, the fast growth rate, high fertility, early sexual maturity, and benthic nature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to environmental pollution, overfishing, and other factors, there has been a sharp decline in the wild resources of H. labeo in many rivers. The artificial breeding of H. labeo has been performed in different regions, such as the Fujiang, Wusuli, Yalu, Liaoning, Oujiang, and Qiantang Rivers, to save this precious resource [21][22][23][24][25]. Moreover, H. labeo has the wide distribution, medium life span, the fast growth rate, high fertility, early sexual maturity, and benthic nature.…”
Section: Introductionmentioning
confidence: 99%
“…The population ecology of H. labeo in many water bodies has been studied, including the Heilongjiang Basin [20,23], the Yangtze River Basin [21,22,27,28], the Pearl River Basin [26] in China, Chikugo River in Japan [29], and Goe-san Lake in Korea [30]. In a study of the reproductive biology of H. labeo in the Ganjiang River of China [27], we observed that the morphological differences between wild female and male individuals are not apparent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation